Knowledge, attitudes, beliefs and practices of health care practitioners towards urinary incontinence management - Janse van Vuuren, Anika Corle (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScPhysio)--Stellenbosch University, 2022.